Capacidades dinâmicas no setor de geração de energia elétrica no Brasil : o caso da CEMIG - Lenzi , Charles (2015)
This study aims to analyze how it occurs the dynamic of the relationship between dynamic capabilities and organizational competences of a Brazilian power generation company that have been impacted by several changes in the regulatory frameworks occurred from the early 1990s to the present day. One major change in the power generation business model was the introduction of a competitive environment and other profound modifications in legislation and operational structure of the entire Brazilian electricity sector. In this new context is likely that companies have reviewed their strategies, reassessing their organizational competences in order to adapt and to continuously achieve their business objectives. In a constantly changing environment, the dynamic capabilities approach has been related to the way by which companies create and capture value through reconfiguring their resources and competences.The research had a qualitative approach and it was conducted through a case study with historical and longitudinal approach on Cemig Generation and Transmission S / A. As a result, it was possible to characterize a subdivision into three historical periods of the company in view of the period from 1990 to 2013. It was also identified three organizational competences of Cemig GT, which have changed over the analyzed historical period, impacted by two dynamic capabilities: the capability to develop alliances and partnerships and the capability to mobilize people for business. The results obtained helped to understand the trajectory of the organization during the study period, indicating that the dynamic capabilities developed by the company have leveraged their organizational competences, contributing to the results the company has achieved.